Evidence of Leptospiral Presence in the Cumberland Gap Region. - Ashutosh Verma; Brittney Beigel; Christopher Carl Smola; Susanna Kitts-Morgan; Daniel Kish; Paul Nader; Joey Morgan; Jerry Roberson; Undine Christmann; Karen Gruszynski; LaRoy Brandt; Ellen Cho; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:Leptospirosis is a widespread zoonotic disease that causes reproductive losses and/or hepatorenal failure in a number of animal species. Wild reservoirs of the disease, such as rodents, harbor the causative bacterium, Leptospira spp., in their kidneys and contaminate the environment by excreting infected urine. In this study, we tested small wild mammals, environmental water, and livestock in the Cumberland Gap region of southeastern Appalachia for the presence of pathogenic Leptospira or leptospiral antibodies. METHODS/RESULTS:Small wild mammals (n = 101) and environmental water samples (n = 89) were screened by a real time quantitative PCR that targets the pathogenic Leptospira-specific lipl32 gene. Kidneys from 63 small wild mammals (62.37%) and two water sources (2.25%) tested positive for leptospiral DNA. To identify the infecting leptospiral species in qPCR-positive water and kidney samples, a fragment of leptospiral rpoB gene was PCR amplified and sequenced. L. kirschneri and L. interrogans were the leptospiral species carried by small wild mammals. Furthermore, sera from livestock (n = 52; cattle and horses) were screened for leptospiral antibodies using microscopic agglutination test (MAT). Twenty sera (38.46%) from livestock had antibodies to one or more serovars of pathogenic Leptospira spp. CONCLUSIONS:In conclusion, results from our study show exposure to leptospiral infection in farm animals and the presence of this zoonotic pathogen in the environmental water and kidneys of a significant number of small wild mammals. The public health implications of these findings remain to be assessed.